2019
DOI: 10.1186/s41983-019-0059-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the risk factors and functional outcome of delirium in acute stroke

Abstract: Background: Post stroke delirium is a multifactorial life-threatening process, still poorly understood. The aim of the study was to identify the risk factors associated with the development of delirium in acute stroke patients and detection of the effect of delirium on the short-term prognosis of acute stroke patients.Patients and methods: This study was carried on 74 acute stroke patients, 40 males (54.1%) and 34 females (45.9%). Full general and neurological examination was performed to all patients. Full ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…After the removal of duplicates, 2137 entries were scanned. Finally, 116 full texts were assessed for eligibility, with 42 articles [ 5 , 6 , 10 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ] fulfilling all criteria. Three additional studies [ 59 , 72 , 73 ] were identified through reference lists, leading to a total of 45 articles that were included in the current meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…After the removal of duplicates, 2137 entries were scanned. Finally, 116 full texts were assessed for eligibility, with 42 articles [ 5 , 6 , 10 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ] fulfilling all criteria. Three additional studies [ 59 , 72 , 73 ] were identified through reference lists, leading to a total of 45 articles that were included in the current meta-analysis.…”
Section: Resultsmentioning
confidence: 99%